Financing Methods and Efficiency of Public Investments in Accordance with Strategic Planning - Benedykt OPALKA; Krzysztof JAROSINSKI (Communications of International Proceedings, 2021)
Financing investments in the public sector can be implemented according to many possible scenarios, depending on the concept and conditions resulting from the established development policy. The financial barrier is particularly important, affecting the possibility of acquiring resources enabling the proper implementation of investment projects. The aim of the paper is to identify the practical financing conditions and the possibility of assessing the efficiency of public investment projects in relation to the requirements resulting from the concept of strategic planning. A strategic approach to development problems provides the basis for prospective analyses of the use of public funds and enables the appropriate selection of sources of financing for investment projects in various entities of the public sector. The study attempts to identify the benefits of implementing the principles and instruments of strategic planning in the investment activity of the public sector, taking into account the quantitative analysis of various investment outlays at the level of the government sector and the local administration sector. The empirical research was to lead to the confirmation of the need for and importance of developing new approaches for better management of public resources in economic practice.
Keywords: Public Sector; Investment; Efficiency; Strategic Planning.